Hedging Strategies in Non-Science Theses: A Corpus-Based Analysis of Discussion Sections - Suratno, Antonius; Aydawati, Emilia Ninik (ETERNAL (English Teaching Journal), 2025)
This study aimed to investigate the academic writings of students, which were stored in the students' theses repository. The primary goal was to explore how students employ politeness and caution strategy, often referred to as academic hedging when articulating their academic opinions in Chapter IV of the discussion section within their theses. Utilizing a corpus-based approach, the study analyzed 30 theses comprising over 100,000 words. The Antconc electronic analysis application was deployed to identify patterns of sentence expression and explore how students employed hedging techniques to present their academic ideas. The results indicate that student writers tended to rely heavily on the modal "dapat" compared to other hedging devices, suggesting a potential lack of familiarity with diverse hedging methods and their appropriate use in academic writing. It is postulated that this overreliance on "dapat" might be attributed to limited exposure to alternative hedging devices in academic writing. This indicates a need for academic writing teachers in universities to equip students with comprehensive knowledge of hedges for more appropriate expression of academic ideas.